Modelling Of A New Fully Hybrid Spectrum Sharing Approach Fifth Generation Cellular Operators - Attiah, Mothana Lafta (2020)
Spectrum sharing approach (SSA) has been emerged as a cost-efficient solution for the enhancement of spectrum utilization to meet the stringent requirements of 5G systems. However, practical issues concerning the implementation of such an approach are rarely addressed such as mutual inter- or intra-operator interference, millimeter wave user association (mUA) suboptimality, the associated infrastructure cost for deploying more mmWave cells, and fairness. Therefore, in this thesis, a new fully hybrid spectrum sharing (FHSS) approach consisting of an efficient mmWave cell–carrier distribution strategy and a new hybrid and adaptive QoE-based mUA algorithm (HAQ-mUA) were proposed with consideration to the interference dilemma. More precisely, the mmWave cell–carrier distribution strategy was implemented by setting up a tolerable distance among the mmWave cells (mCells) that operate at the same band (28 or 73 GHz) which are adopted in this work. The fully hybrid allocation of the spectrum is ensured by considering three spectrum access strategies (licensed, semi-shared, and fully-shared access) in an integrated and hybrid manner. Whereas, the new HAQ-mUA was presented to assign a typical user to the serving mCell, which offers the highest achievable data rate. The proposed FHSS based on the HAQ-mUA algorithm was compared with recent works and with both the FHSS approach based on the most conventional max-SINR mUA algorithm and the baseline scenario (utilizing licensed spectrum access). Numerical results demonstrate the superiority of the proposed FHSS based on the HAQ-mUA algorithm over the baselines approaches (licensed spectrum access strategy and FHSS based on max-SINR mUA algorithm) and the other relevant studies. In terms of system coverage performance, the proposed approach achieves (0%) outage probability with SINR value (>2 dB) of the cell edge users. Whereas, it is observed that the achievable data rate of all the users exceeds 100 Mbps, with an average data rate of more than (1.8X) over the benchmarks. Furthermore, it also proves its effectiveness in distributing the load across the network, where 20.5%–32%, 10.5%–20%, and 59.5%–65% of the users associate with mCells that support the three spectrum access strategies, respectively, reducing the number of mCell to half (16 mCells), thus saving half of the cost of the network infrastructure, and achieving a higher degree of fairness (F_index=0.9608) among the participating operators. This approach may serve as an incentive and encourage operators to share the spectrum with others